PROPOSE BUSINESS STRATEGY DURING ECONOMIC DOWNTURN IN STORAGE TANK SERVICE PROVIDER TO GAIN BACK MARKET SHARES: CASE STUDY AT PT VICTORY TERMINAL MERAK - Hajar, Shinta Siti; Anggoro, Yudo (CV. Radja Publika, 2025)
PT Victory Terminal Merak, a subsidiary of a global storage tank provider headquartered in the Netherlands, has played an important role in supporting Indonesia’s trade and energy infrastructure through its terminal operations in Merak region. For the past 5 years, the company has been facing challenges caused by the global pandemic (COVID-19) and the subsequent global economic downturn triggered by geopolitical tensions and inflations. These external factors have immensely affected operational efficiency, customer retention, and revenue performance. Despite positive growth projections in the Asia Pacific oil and gas storage market, PT Victory Terminal Merak has not been able to fully leverage these opportunities due to outdated commercial strategies and a centralized decision-making structure from the regional office in Singapore. This thesis explores the underlying factors contributing to the terminal’s declining competitiveness, focusing on its sales, and marketing approach, which has not been pacing with evolving customer expectations and local market dynamics. Drawing on a combination of qualitative insights and quantitative findings, this research identifies key internal inefficiencies and external market pressures while introducing a revised commercial direction tailored to the Indonesian context, emphasizing customer-centric practices, greater operational agility, and a cultural shift toward continuous improvement.